Pengaruh Transaksi Digital dan Kedisiplinan Keuangan terhadap Perilaku Konsumtif Santri di Pondok Pesantren Darul Falah - Rissa Alfin Nanda; Nafi’ah Nafi’ah; Setia Dwi Ratna (Lembaga Teewan Journal Solutions, 2026)
This study aims to examine the effect of digital transactions on students’ consumptive behavior, the effect of financial discipline on students’ consumptive behavior, and the combined effect of digital transactions and financial discipline on the consumptive behavior of students at Darul Falah Islamic Boarding School. A quantitative approach was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS 4. The study involved 100 respondents selected through simple random sampling. The findings indicate that digital transactions have no significant effect on students’ consumptive behavior, whereas financial discipline has a significant effect. The R-square value of 0.307 shows that digital transactions and financial discipline jointly explain 30.7% of the variance in consumptive behavior, while the remaining 69.3% is influenced by other factors beyond the scope of this study. Therefore, this study recommends strengthening students’ financial literacy and financial discipline as effective strategies to control consumptive behavior within the Islamic boarding school environment.